Topographic Maps Remodelling When Changing Height System - George Valev; Penka Kastreva; Adib Al-Kamouh (Tishreen University, 2014)
The change of the coordinate and height system in one country as well as the transformation to another height level and system requires compulsory transformation of the local contents and of the represent of the relief. The height transformations are not so insufficient clarified in GIS and CAD products that's why this question is very important and gets really actual nowadays. There are many publications on the way of transforming the elevations of the benchmarks of the existing height systems and the calculation of the corrections of the elevations in the Baltic system in relation to the European Height System with an initial point the gauge in Amsterdam. Unfortunately a methodology for the practical transformation of the contour lines has not been developed yet. In this paper some basic issues and procedures on the practical application, related to the solution of this problem, have been discussed - how to correct the image of the relief, as part of the content of a digital map, while passing from one projection to another, respectively from one coordinate system into another. The problem is inevitably related to the transformation of heights, which is obligatory when changing the Sea level and the Height System. We can use this research and its results in similar studies and researches in SYRIA. إنّ تغيير نظام الإحداثيات ونظام الارتفاعات في بلد ما يتطلّب التحويل إلى نظام ارتفاعي. ويتمّ التشكيل الإلزامي للتفاصيل المحليّة، وإعادة تمثيل تضاريس المنطقة في الجملة الجديدة. إنّ التحويلات الارتفاعيّة ليست كافية وغير موضحة في الدراسات والأبحاث المتعلقة بأنظمة المعلومات الجغرافية GIS ، وأنظمة الرسم  CAD . لهذا يعدُّ هذا السؤال مهماً جداً ويأخذ في الواقع حيّزاً من الدراسات في هذه الأيام. وتوجد مقالات عديدة تبحث في طرق تحويل الارتفاعات إلى مراجع التسوية، حسب أنظمة الارتفاعات المعتمدة، مع حساب تصحيحات المناسيب وفق نظام بحر البلطيق  Baltic System والعلاقة مع نظام الارتفاع الأوروبي European Height System انطلاقاً من النقطة الأوليّة المعتبرة في القياس في مدينة أمستردام. ولسوء الطالع؛ فإنّ منهجية التحويل العملي لخطوط التسوية Contour lines لم تُناقش بعد. تقدّم الورقة البحثيّة بعض النتائج الأساسية والإجراءات في التطبيقات العملية والمتعلّقة بحل هذه المشكلة. فقد نوقشت كيفيّة تصحيح تمثيل التضاريس، كجزء من محتوى الخريطة الرقمية، وذلك عند الانتقال من نظام إسقاط إلى نظام إسقاط آخر، وبالتالي الانتقال من نظام إحداثي إلى نظام إحداثي آخر. إنّ المشكلة متعلّقة حتماً بنظام تحويل الارتفاعات، وهي ضرورية عندما يتغيّر مستوى البحر والنظام الارتفاعي المعتمد. وتُمكننا الاستفادة من هذا البحث ونتائجه في دراسات وأبحاث مماثلة في سورية.